Evaluation of thiol/disulfide homeostasis and ischemia modified albumin as potential markers for periodontitis - Bilge Karcı; Hasan Basri Savas (BMC Oral Health)
Abstract Background The current study aimed to assess the impact of periodontitis on oxidative stress parameters by examining serum total antioxidant capacity (TAS), total oxidant status (TOS), oxidative stress index (OSI), thiol/ disulfide homeostasis and ischemia modified albumin (IMA). Methods The study had 90 participants, categorized into 3 groups: Group 1: Periodontally healthy; Group 2: Stage II Grade B periodontitis; Group 3: Stage III and IV Grade B periodontitis. Demographic and periodontal variables were assessed. The levels of serum TAS, TOS, OSI, IMA, and thiol/disulfide were assessed. Results No significant differences in sex and age were detected among the groups (p > 0.05). When compared to Group 1, all clinical measurements were statistically significantly greater in Group 3 (p < 0.05). Statistical analysis revealed no significant differences in serum TAS, TOS, and OSI levels among the groups (p > 0.05). The highest serum IMA value was observed in Group 3 (p = 0.037), whereas native thiol (p = 0.00), total thiol (p = 0.00) and disulfide values (p = 0.023) were highest in Group 1. Conclusions These findings indicate that thiol/disulfide homeostasis and IMA could hold promise as a potential biomarker of inflammation in periodontitis.